Groupitizing reflects conceptual developments in math cognition and inequities in math achievement from childhood through adolescence. Issue 2 (9th December 2022) - Guillaume, Mathieu; Roy, Ethan; Van Rinsveld, Amandine; Starkey, Gillian S.; ,; Uncapher, Melina R.; McCandliss, Bruce D.
Abstract: Understanding the cognitive processes central to mathematical development is crucial to addressing systemic inequities in math achievement. We investigate the "Groupitizing" ability in 1209 third to eighth graders (mean age at first timepoint = 10.48, 586 girls, 39.16% Asian, 28.88% Hispanic/Latino, 18.51% White), a process that captures the ability to use grouping cues to access the exact value of a set. Groupitizing improves each year from late childhood to early adolescence ( d = 3.29), is a central predictor of math achievement (beta weight = .30), is linked to conceptual processes in mathematics (minimum d = 0.69), and helps explain the dynamic between the ongoing development of non‐symbolic number concepts, systemic educational inequities in school associated with SES, and mathematics achievement (minimum beta weight = .11) in ways that explicit symbolic measures may miss.